The Fundamental Deviation and the Riddle of Manipulation: A Critical Analysis in the Context of Bangladesh Stock Market Crash in 2010-11 - Hossain, Md. Toufique (Asian Business Review, 2014)
The capital market in Bangladesh does not always act based on the fundamentals. Fundamental means the set of ethics, principles, guidance, various market instruments and well structural set up that helps the stock market for operating well. Structural weakness is a thing which may ruin the market base or fundamentals. But the capital market as part of the economy should function based on the fundamental norms, principles and proper rules and regulations. Otherwise, there may be some detrimental effects on the market. Stock market anomalies bring harm not only to destroy market fundamentals but also to spread manipulation inside the stock market. Moreover, the recent stock market crash in 2010-11 was the biggest shock for the 3.3 million innocent and small investors in the capital market of Bangladesh. A section of greedy investors resorted to manipulation at different levels to cash in on the lack of small investors’ proper knowledge about market fundamentals. The excessive fraudulent activities of the unscrupulous manipulators just hastened the fall of the market. So, much of the focus of this study has been put on the causes and consequences of the fundamental deviation and the riddle of manipulation based on the relevant facts and figures. JEL Classification Code: E44, G10